Evaluation of students’ performance in elective mathematics: The effect of high school students’ perceived difficulty of the subject - Asomah, Richard Kyere; Narh-Kert, Millicent; Abdul-Malik , Sakara; Enu, Justice; Koomson, Anthony (Universitas Majalengka, 2024)
Perception has been attributed as a major cause of students' weakness in mathematics. Hence, this study evaluates its effect on student’s performance in the area of mathematics as an elective subject in some selected Senior High School (SHS) in Ghana. Mixed method research design that employed questionnaire with closed-ended and open-ended items were used in the collection of the data. Stratified sampling technique was used in selecting 300 students as sample for the study. Descriptive statistics and Multiple regression were used to analyse the quantitative data. Again, thematic analysis was used for the qualitative data. The findings showed that, SHS students perceived elective mathematics as a difficult subject. Nonetheless, they perceived the teacher-learner activities employed by their teachers in elective mathematics classroom as motivating. Further, they perceived as constructive, the teaching methods used by their elective mathematics teachers. In addition, the study revealed that students’ performance in elective mathematics was not significantly influenced by their perceived difficulty of elective mathematics, teacher motivation and teaching methods although the students expressed favourable dispositions towards these attributes. Thus, the need for Heads of High Schools, to do background check of students’ prior performance, interest and motivation in mathematics as a prerequisite condition for students to pursue elective mathematics is implied in this study. This could stem the tide in the students’ abysmal performance in elective mathematics. Implications for policy, practice and further research are discussed.